Media Audio Visual Untuk Meningkatkan Aktivitas Belajar Siswa Dalam Mengenal Mahluk Hidup - -, Yanemis (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2016)
Audio-Visual Media is the media that has elements of sound and image. These media types have the ability better, because both types of media covering the first and second. Learning activities are activities that are both physical and mental that involve work, the mind, the body, especially in terms of teaching and learning activities to achieve the goals set. This research is a class act, with a sample of students in kindergarten amounted to 24 people with varying abilities. Use of Audio Visual Media can improve learning outcomes of learners in recognizing living things. It can be seen from the study of students who experienced an increase from the first cycle to the second cycle. Mastery learning students in the first cycle of 79.16% and 83.33% in the second cycle. An increase from the first cycle to the second cycle of 4.17% means that student learning outcomes that meet KKM â‰¥ 65 reached 83.33% at the end of the cycle. This increase occurred because keterlaksanaan learning in the second cycle better than the cycle I.